Festival Anak Sholeh sebagai Sarana Penguatan Moderasi Beragama di Tingkat Nagori : Studi Kasus Nagori Marihat Bukit - Adika Pranata; Annisa Khumaira; Arlia Rasita; Muhammad Alfikri; Risky Fauzy Hasibuan (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This study aims to analyze the implementation of religious moderation values through the Festival Anak Islami organized by community service program (KKN) students in Nagori Marihat Bukit. The research employed a descriptive qualitative method with data collected through observation and documentation. The findings reveal that the festival not only serves as a competition platform in Islamic-themed activities such as call to prayer (azan), Qur’an memorization (tahfidz), prayer recitation, quiz competitions, and calligraphy, but also functions as a medium for instilling the values of religious moderation from an early age. Tolerance, sportsmanship, solidarity, and respect for local wisdom were clearly reflected in the interactions among the children, the active participation of the community, and the involvement of local leaders. This activity demonstrates that community-based religious education can strengthen social cohesion, foster inclusiveness, and support the four indicators of religious moderation promoted by the Ministry of Religious Affairs. Therefore, the Festival Anak Islami can be considered an effective model for community-based religious moderation education in building a harmonious and moderate society.